Simulación del gradiente térmico en la dentina radicular con terapia endodóntica láser GaAIAs un estudio de estado estable (2003)
ABSTRACT: Laser therapy has been used for a variety of intraoral applications including sterilization of dental tissues and root canals in endodontic therapy. The distribution of the thermal gradient in root dentine is not very well known, but it is accepted that dentin provides good thermal insulation, however, there are still some concerns regarding the effect of the temperature on the supporting tissues of the teeth. Objective. The purpose of the present study was to evaluate the increases in the temperature on the external surface of the roots of teeth, using a commercial Diode Laser of 810 nm. Methods and Materials. The laser was applied to the internal surface of the root, and 3-D models with Finite Element Method (FEM) were created in order to evaluate the increases in temperature. The three models were created from a transversal cut of a lower incisor with different remnant dentinal walls. The initial conditions were 37 °C as the external temperature of the root, the excitation temperatures for the internal part of the root were obtained experimentally. Results. With the limitations of a simulation in a stable state, a higher temperature was found in the external surface of the root for the thinner walls (1.2 mm) with the three temperatures of excitation evaluated. The results of the simulation associated to 0.5 W of the laser power presented the more biologically compatible increments for the external surface of the root.